The spider genus Uroctea Dufour, 1820 (Araneae: Oecobiidae) in Yemen - Rheims, Cristina A.; Santos, Adalberto J.; van Harten, Antonius (Zootaxa, 2007)
Three species of Uroctea are recorded from Yemen. Uroctea concolor Simon, 1882, the only species of the genus originally described from Yemen, is redescribed and illustrated based on the type specimen. Uroctea sudanensis Benoit, 1966, originally known only from Sudan, is first reported outside Africa. Uroctea thaleri sp.n. is described, illustrated and recorded from other Middle-Eastern and Asian localities based on literature data.